PERAN PRAJURIT KORPS MARINIR DALAM MENJAGA WILAYAH PERBATASAN LAUT SELAT MALAKA (Studi Kasus Batalyon Infantri - 8 Marinir Pangkalan Brandan) - , M Nasir Wahab ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One role of the Indonesian National Army Navy (TNI AL) is to safeguard and secure the jurisdiction of the territorial waters of Indonesia from all threats, whether the threat comes from internal of Indonesia and from abroad. In performing his duties, the Navy is supported by the four components which are known as Sistem Senjata Armada Terpadu (SSAT), the Ship of the republic of Indonesia (KRI), aircraft, marine and base. This research investigated the Marine role in maintaining and securing the Malacca Strait sea border region, the factors that influence this role and strategy or effort that needs to be done to enhance that role. This research was conducted in Batalyon Infanteri-8 Marinir (Yonif-8 Mar) Pangkalan Brandan. Data were obtained by questionairs to the soldiers and interviews. These data were evaluated and statistically analyzed. The result confirm that role of Marine soldiers in maintaining and securing the Malacca Strait is quite good, they understand the importance of their role and have strong motivation to increase their role in maintaining and securing the Malacca Strait sea. To increase the Marine soldiers in maintaining and securing the Malacca Strait, It is necessary to increase the quality and quantity of human resources, perform the training regularly and continuously and complete the Marine soldiers with the facilities required in conducting their duties.